PENGELOLAAN KONFLIK RUMAH IBADAH MELALUI PENDEKATAN STRUKTURAL DAN KULTURAL: KASUS PENDIRIAN VIHARA TRI DHARMA DI KEDAMAIAN KOTA BANDAR LAMPUNG: CONFLICT MANAGEMENT ON HOUSES OF WORSHIP WITH STRUCTURAL AND CULTURAL APPROACH: THE CASE OF TRI DHARMA VIHARA ESTABLISHMENT AT KEDAMAIAN BANDAR LAMPUNG - Daniel Rabitha (Penamas, 2014)
The houses of worship establishment is frequently being the cause of conflicts among religious communities. Hence, it is important to know the management of the houses of worship establisment to avoid conflict. This research is a case study of setting up Tri Dharma Vihara in Kelurahan Kedamaian, Kota Bandar Lampung. The study concluded that, the case is one example in understanding the conflict management mechanisms of houses of worship establishment in Bandar Lampung city. It is shown that the government interfere through PBM Number 9 and 8 of 2006 is a planning step to constructively manage conflict of houses of worship establishment. This conflict resolution through PBM is done structurally and culturally. In structural context, the resolution can be seen from organizing effort of the parties related to conflict resolution. In cultural context, the parties related to conflict resolution have done facilitating efforts to resolve the conflict.Keywords: Conflict management, the houses of worship establishment, vihara, monastery, Lampung.Pendirian rumah ibadah sering menjadi faktor penyebab munculnya konflik antar umat beragama, karena itu penting diketahui pengelolaan pendirian rumah ibadah agar tidak menimbulkan konflik. Penelitian ini merupakan studi kasus pendirian Vihara Tri Dharma di Kelurahan Kedamaian, Kota Bandar Lampung. Penelitian menyimpulkan, bahwa kasus pendirian Vihara Tri Dharma menjadi salah satu contoh dalam memahami mekanisme pengelolaan konflik pendirian rumah ibadah di Kota Bandar Lampung. Hal itu ditunjukkan oleh andil pemerintah melalui PBM Nomor 9 dan 8 Tahun 2006 yang merupakan langkah perencanaan dalam mengelola konflik pendirian rumah ibadah secara konstuktif. Dalam pengelolaan konflik tersebut, penanganan konflik melalui PBM dilakukan secara struktural dan kultural. Secara strukural jelas terlihat pada pengorganisasian dari pihak-pihak terkait dalam penyelesaian konflik. Secara kultural terlihat pada upaya fasilitatif dari pihak-pihak terkait melalui musyarawah dalam penyelesaian konflik.Kata Kunci: Manajemen konflik, pendirian rumah ibadah, vihara, Lampung.